Sumbangan Syarif Hidayatullah dalam Penyebaran Pendidikan Agama Islam di Jawa Barat - Mohd Roslan Mohd Nor; Cecep Miftahul Hasani (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
This article discusses the contribution of Syarif Hidayatullah in spreading Islam in the West of Jawa, Indonesia. This research is qualitative and historical studies. Existence of historical facts through text, structure, and culture became a reference in the study. The purpose of this paper is to describe the contributions related to the spread of Islam by Syarif Hidayatullah. Indication of his contribution in the spreading Islam was visible from some areas within the society. His contribution includes in the area of social, economic, cultural, artistic, spatial (dealing with space) and political. Syarif Hidayatullah treasures contribution in public life can be noticed when it has a strong influence on the development of the society in various fields. The essence of his activism is how the spread of Islam can thrive through the changes that happened within the society which inspire changes in various fields, especially in this Nusantara region.